A systematic approach for developing course learning outcomes to fulfill accreditation requirements in Malaysia - Elsheikh, Elsheikh Mohamed Ahmed; Sarudin, Isarji; Gunawan, Teddy Surya (IEEE, 2018)
Writing appropriate learning outcomes is crucial to course design. Properly written outcomes aids the design of other course elements such as delivery methods and assessment. This paper proposes a systematic approach for writing learning outcomes. The proposed procedure takes advantage of the hierarchical structure of the programme building components. When applied, the procedure helps meet some of the accreditation requirements imposed by the Malaysian Engineering Accreditation Council such as explicit assessment of programme outcomes. Key to success is the careful mapping between course components. Besides, the procedure simplifies course design consequently leading to continual improvement. The procedure can be applied to wide range engineering courses. It also gives more control on planning a balanced assessment.